Exculpation as a punitive criteria against crimes related to rebellion in contexts of internal armed conflict: A rereading of the criminal law work in pacification processes - Lucero Pantoja, Jairo Enrique (2020)
One of the most conflictive scenarios for criminal law and its punitive and preventive responses is found at the confluence of armed conflicts, being these an inexhaustible engine of production of regulated criminal acts, both nationally and internationally. The present work will focus its study on those crimes related to internal armed conflicts and on how we can reach a more comprehensive legal logic from a dogmatic criminal perspective derived from the theory of crime —more than a political response in amnesty—, specifically through assumptions of need, when providing a definitive resolution to a context of armed conflict, which requires unrestricted criminal solutions to the dialectical borders of each government in office.